B-cell depletion improves therapeutic index of combination checkpoint blockade in patients with advanced melanoma - Kavita M. Dhodapkar; Antonio Matera; Alyssa M. Duffy; Azmain Taz; Renee Julia Manalo; Melinda Yushak; Ragini Kuchadkar; David H. Lawson; Madhav V. Dhodapkar (Journal of Clinical Investigation, 2026)
Background: Combined checkpoint blockade (CCB) of programmed-death-1 (PD-1) and cytotoxic-T-lymphocyte-associated protein-4 (CTLA-4) is highly active in melanoma but limited by significant morbidity from immune-related adverse events (irAEs). Effective strategies to prevent CCB-mediated irAEs are lacking. Methods: Patients with advanced melanoma were randomly assigned to receive standard of care ipilimumab and nivolumab alone (Arm-A: ipi/nivo, n=7) or with one cycle of rituximab (Arm-B; ipi/nivo+rituximab, n=7). Results: Patients receiving ipi/nivo+rituximab experienced lower rates of > grade-3(G3) irAEs (14% versus 57%) and superior G3-irAE-free survival compared to those in ipi/nivo arm (2-year G3-irAE-free survival 86% versus 29% (p=0.01), without adverse impact on tumor regression or survival. G3 hypersensitivity reactions to rituximab (43% in Arm-B) prompted trial closure. Rituximab depleted pre-therapy activated naïve B cells linked to autoimmunity and enhanced CCB-mediated induction of myeloid inflammation and CXCL13+ICOS+ CD4 T cells. Conclusion: B-cell depletion favorably modulates CCB-mediated immune activation and may reduce irAE risk. Trial Registration: ClinicalTrials.gov NCT03719131 Funding: NIH